2020
DOI: 10.3390/en13225941
|View full text |Cite
|
Sign up to set email alerts
|

Maximising Yield and Engine Efficiency Using Optimised Waste Cooking Oil Biodiesel

Abstract: In this study, waste cooking oil (WCO) was used as a feedstock for biodiesel production, where the pretreatment of WCO was performed using mineral acids to reduce the acid value. The response surface methodology (RSM) was used to create an interaction for different operating parameters that affect biodiesel yield. The optimised biodiesel yield was 93% at a reaction temperature of 57.50 °C, catalyst concentration 0.25 w/w, methanol to oil ratio 8.50:1, reaction stirring speed 600 rpm, and a reaction time of 3 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…The power maximum of B20 was 3% lower compared with B0 and a similar result has been reported by K.A Abed et al, A.M Liaquat et al and Luqman R et al [19][20][21]. The emission testing results showed that B20 could reduce CO and HC emissions at all travel distances.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The power maximum of B20 was 3% lower compared with B0 and a similar result has been reported by K.A Abed et al, A.M Liaquat et al and Luqman R et al [19][20][21]. The emission testing results showed that B20 could reduce CO and HC emissions at all travel distances.…”
Section: Discussionsupporting
confidence: 83%
“…Laboratory tests at every traveled distance showed that the biodiesel B20 has a lower fuel economy compared with B0, but only after a distance of 20,000 km and only up to 40,000 km. The lower fuel consumption of this biodiesel was caused by the lower heating value of B20 [15][16][17][18][19][20][21], but an improvement in the standard settings of the engine could be considered, as the deterioration of the engine components with B20 was only a little bit better compared to diesel fuel. Moreover, fuel economy testing in this study was conducted in a laboratory following the New European Driving Cycle (NEDC), which did not require full pedals for vehicles to follow the cycle.…”
Section: Discussionmentioning
confidence: 99%
“…A higher performance for diesel was also observed mainly due to this reason. A higher peak was observed for SuOME than diesel under diffusion during the phase [65]. Hence combustion rates were higher during later stages of combustion with SuOME.…”
Section: Combustion Analysismentioning
confidence: 87%
“…Many researchers reported that diesel engines using producer gas emit lower smoke and NO X with little compromise in thermal efficiency [1,[15][16][17]. It was reported that the operation of the engine in dual fuel mode at lower loads causes underutilization of gaseous fuel resulting in lower thermal efficiency and higher CO, HC emissions than the operation with diesel [18][19][20][21][22]. Using the producer gas in dual-fuel CI engines will save about 60-80% of pilot fuel and 100% fossil fuel if biodiesel is used.…”
Section: Introductionmentioning
confidence: 99%